Antioxidant responses of triangle sail mussel Hyriopsis cumingii exposed to harmful algae Microcystis aeruginosa and high pH. (March 2020) - Liu, Yimeng; Li, Lei; Zheng, Liang; Fu, Ping; Wang, Yu; Nguyen, Haidang; Shen, Xiaosheng; Sui, Yanming
Abstract: In lakes and reservoirs, harmful algal blooms and high pH have been deemed to be two important stressors related to eutrophication, especially in the case of CO2 depletion caused by dense blooms. However, the effects of these stressors on the economically important shellfish that inhabit these waters are still not well-understood. This study evaluated the combined effects of the harmful algae Microcystis aeruginosa (0%, 50%, and 100% of total dietary dry weight) and high pH (8.0, 8.5 and 9.0) on the antioxidant responses of the triangle sail mussel H. cumingii . The mussels were exposed to algae and high pH for 14 d, followed by a 7-day depuration period. Reactive oxygen species (ROS) in the mussel hemolymph, antioxidant and detoxifying enzymes, such as glutathione-S-transferase (GST), glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and malondialdehyde (MDA) in the digestive glands were analyzed during the experimental period. GST, SOD and GPx activity levels and the content of GSH increased following exposure to toxic M. aeruginosa, whereas CAT activity was inhibited. pH showed no significant effects on the immune defense mechanisms and detoxification processes. However, a high pH could cause increased ROS and MDA levels, resulting in oxidative injury. After a 7-day depuration period, exposure to toxic M. aeruginosa or high pH resulted in latent effects for most of the examined parameters. The treatment group exposed to the highest pH (9.0) displayed an increased oxidation state compared with the other pH treatments (8.0 and 8.5) for the same concentrations of toxic M. aeruginosa . The trends observed for ROS, MDA, GPx, GST, SOD and GSH levels indicated that a high density of toxic algae could result in severe and continuous effects on mussel health. Graphical abstract: Image 1 Highlights: The comprehensive effects of toxic cyanobacteria and high pH on mussels were assessed. Interaction between cyanobacteria and high pH on physiological indicator were found. Compare to high pH, toxic M. aeruginosa induce more severe oxidative stress response. Toxic algae or high pH exposure history showed latent effects on Hyriopsis cumingii.